2007
DOI: 10.1007/s00442-007-0917-6
|View full text |Cite
|
Sign up to set email alerts
|

Does attraction to frugivores or defense against pathogens shape fruit pulp composition?

Abstract: Fruit traits evolve in response to an evolutionary triad between plants, seed dispersers, and antagonists that consume fruits but do not disperse seeds. The defense trade-off hypothesis predicts that the composition of nutrients and of secondary compounds in fruit pulp is shaped by a trade-off between defense against antagonists and attraction to seed dispersers. The removal rate model of this hypothesis predicts a negative relationship between nutrients and secondary compounds, whereas the toxin-titration mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 49 publications
2
71
3
2
Order By: Relevance
“…The fruit removal rate of ornithochoric fruits may reflect the amount of nutrients available to birds (Cazetta et al 2008), and varies from lipid rich fruits with high removal rate (e.g. Cabralea canjerana, Pizo 1997), to non-reward fruits with a very low removal rate (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The fruit removal rate of ornithochoric fruits may reflect the amount of nutrients available to birds (Cazetta et al 2008), and varies from lipid rich fruits with high removal rate (e.g. Cabralea canjerana, Pizo 1997), to non-reward fruits with a very low removal rate (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Fruit lipids and secondary compounds are good predictors of fruit removal (Cazetta et al 2008), what gives room for frugivores exert evolutionary pressure upon these traits, but variation across species in fruit chemistry is also determined to a large extent by common ancestry (Jordano 1995). Stiles (1993), for example, found that captive birds prefer lipid-rich fruits (but see Johnson et al 1985, Borowicz 1988, whereas mammals tend to avoid them (Debussche & Eisenmann 1989, Herrera 1989.…”
Section: Community-wide Patterns Of Chemical Contentmentioning
confidence: 99%
“…Fleshy fruit traits (color, morphology and chemistry) are thought to be an adaptation to their major seed dispersers or to major seed predators, such as pathogens (Herrera 1982, van der Pijl 1982, Cipollini and Levey 1997, Cazetta et al 2008. During the last decades, numerous studies on seed dispersal systems analyzed the fruit morphology and chemical characteristics, but most of these studies were species-oriented, and few took the entire community into consideration (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Diversas características de frutos carnosos podem influenciar na atração e na competição por dispersores (Galetti et al, 2011), as principais são cor (Cazetta et al, 2009;Melo et al, 2011), constituintes químicos (Cazetta et al, 2008) e morfologia (Janson, 1983;Levey, 1987;Gasperin & Pizo, 2012). Espécies que produzem frutos pequenos e em grandes quantidade são classificadas na literatura como generalistas (Howe & Estabrook, 1977), atraindo uma ampla variedade de espécies de aves, muitas das quais empregam frutos em sua dieta apenas ocasionalmente (Fleming et al, 1987;Francisco & Galetti, 2002;Athiê & Dias, 2012).…”
Section: Discussionunclassified